EDUKASI PENCEGAHAN CYBERBULLYING PADA SISWA SMK 1 SUKOHARJO PRINGSEWU, LAMPUNG - wigati, Meilia (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
This The rapid advancement of technology and the internet has greatly facilitated human interaction and communication. However, alongside its benefits, the swift development of the internet also brings negative impacts, such as cyberbullying behavior. Therefore, it is crucial to promote the wise use of social media to raise awareness, particularly among school children, about the dangers of its misuse. The community service program at SMK 1 Sukoharjo aims to enhance students' understanding of how to use social media properly and responsibly, and to avoid engaging in cyberbullying in their daily lives. Through this outreach and education, students are provided with detailed explanations and engage in discussions about the benefits of social media as well as the risks associated with cyberbullying in the digital world.